Development and modeling of technological scheme of steam methane reforming with oxy-fuel combustion and carbon capture - Rogalev, N.D.; Rogalev, A.N.; Kindra, V.O.; Kovalev, D.S.; Vegera, A.N. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
At present, the most common technology for hydrogen production is steam methane reforming. Its key disadvantage is significant emissions of carbon dioxide into the atmosphere due to the presence of natural gas combustion in the air in the reformer furnace. This problem can be solved by switching to oxygen combustion of organic fuel. This paper presents the results of developing a new process flow diagram for a steam methane reforming and a comparative analysis of its energy and environmental characteristics with the closest analogue: steam methane reforming with monoethanolamine cleaning of exhaust gases. To perform a thermodynamic analysis of process flow diagram options using the Aspen Plus software package, mathematical models have been developed that include sequentially solved equations for the processes of oxygen combustion of fuel, steam reforming reaction, steam shift reaction and monoethanolamine absorption reaction at variable pressure. In addition, the modeling took into account the possibility of two side reactions: steam reforming of carbon monoxide and carbon dioxide reforming of methane. The NIST REFPROP database was used to determine the thermodynamic properties of the substances. The thermodynamic analysis showed that for the proposed flow chart of the oxygen-fired methane steam methane reforming, an increase in temperature from 850 to 1050 °C results in a 14.4 % decrease in the mass flow rate of natural gas. At the same time, the thermodynamically optimal temperature in the reformer, equal to 950 °C, provides the possibility of achieving the fuel HUF value of 79.2 %. In turn, the comparison of the energy and environmental characteristics of the two considered steam methane reforming units allowed us to conclude that the proposed flow chart with oxygen-fired fuel has two advantages over the flow chart with CO2 capture by absorption in monoethanolamine: higher energy efficiency (net efficiency is 2.12 % higher) and lower greenhouse gas emissions (carbon dioxide emissions are 14.5 times lower). The proposed process flow diagram, as well as the developed mathematical models, can be used in the development of highly efficient steam methane conversion plants with minimal emissions of harmful substances into the atmosphere.